Digital engagement : internet marketing that captures customers and builds intense brand loyalty - Harden, Leland (American Management Association, 2009)
In an age of overwhelming Internet competition and rampant takeovers, marketers face the very real challenge of understanding how to engage customers online. Leland Harden and Bob Heyman, online marketing pioneers and authors of the popular book Net Results, team up again to teach marketers how to use search engine optimization, affiliate marketing, and all of the Web 2.0 tools they need to compete in the digital marketplace. Filled with up-to-date information on the best venues for online marketing, as well as explanations of social networking, virtual worlds, widgets, wikis, and emerging med.